The legal concept of possession - الموسوي علي فوزي; العامري اندلس حامد (Journal of Legal Sciences, 2019)
The acquisition is of one of the methods utilized by the holding company to expand its activities and its control over other companies. Acquisition activity of the holding companies is particularly important to distinguish them from the rest of the commercial companies. Economic changes in Iraq and the country’s need for foreign capitals havethe multiple and diverse of experiences, leading to, besides the need for a certain technique to increase the competitiveness and financial efficiency capabilities in companies, push the economy towards openness and allow for foreign companies, like national companies, to exercise its business in Iraq and to revitalize the financial market to ensure companies enter new markets through which they can multiply and expand their activities and enrich their financial position in the local, regional and global markets, especially if these financial markets increase the demand for the company’s products interested in acquisitions.